(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This study explores the role of silent movies as a shared experience during the early twentieth century in the United States. Amid high immigration rates, non-English-speaking citizens faced economic and social challenges, including exclusion from public entertainment and discourse. Drawing evidence from reviews, personal correspondence, and diaries, our research demonstrates that silent films served as an affordable and inclusive form of entertainment. We argue for the accessible economic and representational nature of early cinema, evident in low admission prices and actors’ exaggerated gestures that transcended language barriers.